Logistics operations, supply chain management and sustainability - Golinska, Paulina (EcoProduction, Environmental Issues in Logistics and Manufacturing, 2014)
The goal of this book is to present a cross-section of research and applications where simulation and optimization technologies have and can enhance sustainability in logistics and manufacturing. Simulation involves developing a model or representation of a real system, using the model to conduct experiments, and analyzing system performance, all virtually. Thus, simulation is an effective means to assess alternative configurations of a system's design and operation without being intrusive to the real system. Simulation is also often used to assess performance before the system actually exists. By its very nature the process of simulation is sustainable in that it conserves resources and reduces risks. However, simulation by itself, and when coupled with optimization, provides a powerful means to understand a system's behavior and performance, the interactions of its components, its dynamics, the influence of variability, and the effects of changes in system parameters, policies, and the environment. While simulation has been applied in many areas, a review of the literature shows a void in books focusing on the application of simulation and optimization to support the design, analysis, and management of sustainable manufacturing and logistics systems. Similarly, much has been written about sustainability and the use of simulation to assess and improve sustainability, but again, there is a void in its application to manufacturing and logistics. Therefore, the goal of this book is to present a cross-section of research and applications where simulation and optimization technologies have and can enhance sustainability in logistics and manufacturing.